Bouveret's Syndrome: Case Report and Review of the Literature. (11th March 2009) - Doycheva, Iliana; Limaye, Alpna; Suman, Amitabh; Forsmark, Christopher E.; Sultan, Shahnaz
Abstract : Bouveret's syndrome is defined as gastric outlet obstruction caused by duodenal impaction of a large gallstone which passes into the duodenal bulb through a cholecystogastric or cholecystoduodenal fistula. Initial attempts at endoscopic retrieval with or without mechanical or extracorporeal lithotripsy should be performed as first-line treatment, though success rates with endoscopic treatment are variable. We describe a case of Bouveret's Syndrome in an elderly patient that was successfully treated with endoscopic extraction combined with mechanical lithotripsy, and review the literature on this uncommon condition.